Reversed intestinal malrotation presenting as bowel obstruction in pregnancy: Case report and literature review. (October 2022) - Bhartiya, Anjali; Maqsood, Hamza; Naeem, Hamna; Nazar, Muhammad Wajeeh
Abstract: Introduction: Midgut malrotation is a congenital condition caused by insufficient normal intestinal rotation following physiologic gut herniation. Reverse rotation of the midgut is the rarest kind of intestinal malrotation, accounting for about 2%–4% of all cases. Case presentation: We report a case of a 26-year-old South Asian gravida with a previous history of quadruple miscarriage and ovulation induction, presented as intestinal obstruction due to reverse malrotation. An MRI of the abdomen indicated that the mesentery had become twisted around the SMA, resulting in a "whirlpool" pattern. Open exploration was done to accomplish lysis of restricting bands with appendectomy. Conclusion: Intestinal obstruction in pregnancy is uncommon, but when unrecognized in a timely fashion, it is associated with significant maternal and fetal mortality. A simple release of constricting bands without antimesenteric transposition seems to be the safest option in this situation. Highlights: Midgut malrotation is a congenital condition caused by insufficient normal intestinal rotation following physiologic gut herniation. Intestinal obstruction in pregnancy is uncommon, but when unrecognized in a timely fashion, it is associated with significant maternal and fetal mortality. A simple release of constricting bands without antimesenteric transposition seems to be the safest option in this situation.